2022
DOI: 10.13057/biodiv/d230760
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antioxidant activity of methanol extract of Dillenia excelsa leaf

Abstract: Abstract. Lisdiani, Susanto D, Manurung H. 2022. Phytochemical screening and antioxidant activity of methanol extract of Dillenia excelsa leaf. Biodiversitas 23: 3827-3835. The aim of this study was to determine the phytochemical compounds, total flavonoid, and phenolic content, and antioxidant activity of the methanol extract of Dillenia excelsa (Jack) Martelli ex Gilg (or tanikkara) leaves. Sample D. excelsa leaves were obtained from swamp forests in Melintang Village, Muara Wis sub-district, Kutai Kartanega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Punti contains secondary metabolites, such as phenolic compounds, flavonoids, saponins, tannins, and terpenoids (Furqan and Putri 2020). These secondary metabolites can lower blood glucose (Lisdiani et al 2022) by increasing insulin secretion (Martin and Ramos 2021) and/or regenerating pancreatic β cells (Ghorbani et al 2019). In addition, these secondary metabolites also lower blood glucose by increasing insulin sensitivity through the stimulation of insulin receptors (Xu et al 2018) on insulin target cells, such as adipose cells (Kang and Chiang 2022), liver cells, and muscle cells (Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Punti contains secondary metabolites, such as phenolic compounds, flavonoids, saponins, tannins, and terpenoids (Furqan and Putri 2020). These secondary metabolites can lower blood glucose (Lisdiani et al 2022) by increasing insulin secretion (Martin and Ramos 2021) and/or regenerating pancreatic β cells (Ghorbani et al 2019). In addition, these secondary metabolites also lower blood glucose by increasing insulin sensitivity through the stimulation of insulin receptors (Xu et al 2018) on insulin target cells, such as adipose cells (Kang and Chiang 2022), liver cells, and muscle cells (Hu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Matusin et al (2021) examined the methanol extract of Dillenia excelsa leaves. These leaves have antihyperglycemic properties because of the triterpenoid compound effects: flavonoids, tannins, and phenolics (Lisdiani et al 2022). Meanwhile, Furqan and Putri's (2020) found that the ethanol extract of punti contains flavonoids, terpenoids, phenolics, tannins, and saponins.…”
Section: Introductionmentioning
confidence: 99%
“…East Kalimantan is one of the provinces in Indonesia located in a tropical rainforest with several potential endemic florae. Some of these endemic plants from Kalimantan have been proven to have medicinal properties, including tabat barito (Ficus deltoidea), dayak onions (Eleutherine bulbosa), pasak bumi (Eurycoma longifolia), kayu kuning (Arcangelisia flava), karamunting (Rhodomyrtus tomentosa) (Sutomo et al 2013;Manurung 2018), lai (Durio kutejensis), mekai (Albertisia papuana) (Priyanti 2012;Nurbani and Sumarmiyati 2015) and tanikkara (Dillenia exelsa) (Lisdiani et al 2022). The use of plants as a source of medicine has been inherited and is an important component of the health care system.…”
Section: Introductionmentioning
confidence: 99%